2012
DOI: 10.1371/journal.pone.0034971
|View full text |Cite
|
Sign up to set email alerts
|

The Chemokine CXCL12 Is Essential for the Clearance of the Filaria Litomosoides sigmodontis in Resistant Mice

Abstract: Litomosoides sigmodontis is a cause of filarial infection in rodents. Once infective larvae overcome the skin barrier, they enter the lymphatic system and then settle in the pleural cavity, causing soft tissue infection. The outcome of infection depends on the parasite's modulatory ability and also on the immune response of the infected host, which is influenced by its genetic background. The goal of this study was to determine whether host factors such as the chemokine axis CXCL12/CXCR4, which nota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…This need to be taken into account while the objective of the study is to search for genetic or protective mechanisms involved in the control of L. loa microfilaria in a given population. However, the fact that microfilaremia did not exceed 34% while the serological test shows that 100% of individuals have been infected, suggests the existence of genetic factor which limit microfilaria appearance in only some individuals (Bouchery et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This need to be taken into account while the objective of the study is to search for genetic or protective mechanisms involved in the control of L. loa microfilaria in a given population. However, the fact that microfilaremia did not exceed 34% while the serological test shows that 100% of individuals have been infected, suggests the existence of genetic factor which limit microfilaria appearance in only some individuals (Bouchery et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…The phenomenon can be under control of some genetic factors as it was noticed in other parasitic infections (Wakelin and Blackwell, 1988;Bouchery et al, 2012). This study was carried out in the light of new tools for diagnosis to understand whether the absence of microfilaria is just time dependent or a genetic character for some people.…”
Section: Introductionmentioning
confidence: 92%
“…It has been recently shown that abrogation of the chemokine CXCL12/CXCR4 axis that is involved in immune surveillance, favors L. sigmodontis infection. Paradoxically, the CXCL12/CXCR4 axis appears to have a dual effect on its life cycle acting as a host‐cell restriction factor for infection, and as a growth factor for worms . This is especially relevant for filarial pathology as chronically infected, but asymptomatic individuals express lower CXCR4 on T cells as compared to both uninfected and resistant individuals and lymphatic endothelial cells express CXCL12 .…”
Section: Host–parasite Interaction Plays a Key Role In Disease Pathogmentioning
confidence: 99%
“…In this context, we have identified a compound that belongs to this category of pharmacological agents ( i.e. a small neutralizing compound binding to CXCL12), chalcone 4 (Scheme 1), which prevents CXCL12 binding either to CXCR4 or CXCR7 (21, 23, 24, 26, 43, 44). Chalcone 4 blocks responses of CXCR4 to CXCL12 in vitro without affecting the basal level receptor activity and displays anti-inflammatory effects in a murine model of asthma in vivo .…”
Section: Introductionmentioning
confidence: 99%